Caring for People With Dementia Under COVID-19 Restrictions: A Pilot Study on Family Caregivers - Carbone, Elena; Palumbo, Rocco; Di Domenico, Alberto; Vettor, Silvia; Pavan, Giorgio; Borella, Erika (Frontiers in Aging Neuroscience, 2021)
Introduction The present pilot study examined to what extent the COVID-19 lockdown affected the behavioral and psychological symptoms of dementia (BPSD) in people with dementia and worsened their family caregivers’ distress. The associations between changes in the BPSD of relatives with dementia (RwD) and in their caregivers’ distress, and sense of social and emotional loneliness, and resilience were also investigated. Materials and Methods Thirty-five caregivers of RwD attending formal healthcare services before the COVID-19 lockdown volunteered for the study, and were interviewed by phone during the lockdown. Caregivers completed the NeuroPsychiatric Inventory (NPI) to assess their care recipients’ BPSD and their own distress, and two questionnaires assessing their social and emotional loneliness, and their resilience. Results No clear changes emerged in either the BPSD of the RwD or the caregivers’ distress during lockdown compared with before the pandemic. Caregivers reporting more frequent and severe BPSD in their RwD before the lockdown scored higher on emotional loneliness. Those reporting more frequent and severe BPSD under lockdown, especially men and those taking care of RwD with more advanced dementia, scored higher on both social and emotional loneliness. A significant negative correlation also emerged between caregivers’ resilience and changes in their level of distress due to the lockdown, with female caregivers reporting greater resilience. Discussion Our findings offer preliminary insight on the effects of loneliness and resilience, and on the influence of individual characteristics on the experience and consequences of informal caregiving for RwD in times of restrictions imposed by a pandemic.